ANALISIS BIBLIOMETRIK TERHADAP VARIABEL MODERASI DALAM HUBUNGAN ANTARA CSR DAN NILAI PERUSAHAAN - Anak Agung Ayu Prasasti Ayundari; Aang Kunaifi (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This study aims to analyze the development of the literature on the role of moderating variables in the relationship between corporate social responsibility (CSR), environmental, social, and governance (ESG), and firm value through a bibliometric approach and a systematic literature review (SLR). Research data were obtained from the Scopus database using keywords related to CSR, ESG, firm value, and moderating effect. The screening process was conducted based on the fields of business, management, and accounting research as well as the type of research article, resulting in 199 relevant articles for analysis. Bibliometric analysis was performed using VOSviewer and Biblioshiny to identify publication trends, country contributions, journals, the most influential articles, and research theme mapping. The results of the study indicate that publications on moderating variables in the relationship between CSR/ESG and firm value increased significantly during the 2013–2026 period, with China being the country with the largest contribution to these publications. Co-occurrence network and word cloud analyses reveal that firm value, CSR, ESG, corporate governance, financial performance, and sustainability are the main themes of the research. Furthermore, prior research has been dominated by quantitative approaches using regression analysis and moderating variables such as firm size, corporate governance, profitability, and green innovation. These findings suggest that the relationship between sustainability implementation and firm value is contextual and influenced by various dynamic moderating factors.